PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI UD.YUDITA DESA NDARO HILISIMAETANO - Fenima Laia (Universitas Nias Raya, 2023)
This study aims to determine the effect of service quality on consumer satisfaction at UD. Yudita Ndraso Hilisimaetano. This type of research is a causal quantitative research. The sample in this study amounted to 100 consumers. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that there is a significant influence between service quality on consumer satisfaction at UD. Yuditas Village Ndraso Hilisimaetano. In this study, a simple linear regression equation was obtained, namely Y = 24.008 + 0.565X, the obtained t value 5.128 > t table 1.661 and a significant level of 0.000 < 0,05 then the decision was Ha accepted H0 is rejected with the meaning that the service quality variable has a positive and significant effect on consumer satisfaction. The results of hypothesis testing (t test) t value obtained a value of 5.128 > t table value of 1.661 with 100 degrees of freedom (100-2) at a = 0.05 because 0.000 < 0.05, it can be concluded that service quality affects the consumer satisfaction in the UD. Yudita village Ndraso Hilisimaetano.